Maternal Smoking during Pregnancy and the Risk for Childhood Infectious Diseases in the Offspring: A Population-Based Cohort Study - Dan, Nadav; Sheiner, Eyal; Wainstock, Tamar; Marks, Kyla; Kessous, Roy (American Journal of Perinatology, 2019)
Objective Infectious diseases account for up to 43% of childhood hospitalizations. Given the magnitude of infection-related hospitalizations, we aimed to evaluate the effect of maternal smoking during pregnancy on the risk for long-term childhood infectious morbidity.Study Design This is a population-based cohort analysis comparing the long-term risk for infectious diseases, in children born to mothers who smoked during pregnancy versus those who did not. Infectious diseases were predefined based on International Classification of Diseases, Ninth Revision codes. Deliveries occurred between the years 1991 and 2014.Results A total of 246,854 newborns met the inclusion criteria; 2,986 (1.2%) were born to mothers who smoked during pregnancy. Offspring of smokers had significantly higher risk for several infectious diseases during childhood (upper respiratory tract, otitis, viral infections, and bronchitis) as well as increased risk for total infection-related hospitalizations (odds ratio = 1.5, 95% confidence interval [CI]: 1.3–1.7; p = 0.001). Cumulative incidence of infection-related hospitalizations was significantly higher in offspring of smokers (log-rank test, p = 0.001). Controlling for maternal age, diabetes, hypertensive disorders, and gestational age at index delivery, smoking remained an independent risk factor for infectious diseases during childhood (adjusted hazard ratio = 1.5, 95% CI: 1.3–1.6; p = 0.001).Conclusion Intrauterine exposure to maternal smoking may create an environment leading to an increased future risk for long-term pediatric infectious morbidity of the offspring.
Keywords: maternal smoking during pregnancy; intrauterine exposure; pediatric infectious morbidity